Five‐year maintenance of clinical response and health‐related quality of life improvements in patients with moderate‐to‐severe psoriasis treated with guselkumab: results from VOYAGE 1 and VOYAGE 2. (1st December 2021) - Reich, K.; Gordon, K. B.; Strober, B. E.; Armstrong, A. W.; Miller, M.; Shen, Y. K.; You, Y.; Han, C.; Yang, Y. W.; Foley, P.; Griffiths, C. E. M.
Summary: Background: Psoriasis is a chronic disease requiring long‐term therapy. Objectives: Physician‐ and patient‐reported outcomes were evaluated through week 252 in VOYAGE 1 and VOYAGE 2. Methods: In total, 1829 patients were randomized at baseline to receive guselkumab 100 mg every 8 weeks, placebo or adalimumab. Patients receiving placebo crossed over to guselkumab at week 16. Patients receiving adalimumab crossed over to guselkumab at week 52 in VOYAGE 1, and randomized withdrawal and retreatment occurred at weeks 28–76 in VOYAGE 2; all patients then received open‐label guselkumab through week 252. Efficacy and health‐related quality of life (HRQoL) endpoints were analysed through week 252. Safety was monitored through week 264. Results: The proportions of patients in the guselkumab group who achieved clinical responses at week 252 in VOYAGE 1 and VOYAGE 2, respectively, were 84·1% and 82·0% [≥ 90% improvement in Psoriasis Area and Severity Index (PASI)]; 82·4% and 85·0% [Investigator's Global Assessment (IGA) 0 or 1]; 52·7% and 53·0% (100% improvement in PASI) and 54·7% and 55·5% (IGA 0). HRQoL endpoints were achieved as follows: 72·7% and 71·1% of patients (Dermatology Life Quality Index 0 or 1: no effect on patient's life); 42·4% and 42·0% [Psoriasis Symptoms and Signs Diary (PSSD) symptom score = 0] and 33·0% and 31·0% (PSSD sign score = 0). As measured in VOYAGE 2 only, approximately 45% of patients achieved ≥ 5‐point reduction in Short Form‐36 physical and mental component scores, and 80% reported no anxiety or depression (Hospital Anxiety and Depression Scale scores < 8). Similar findings were reported for adalimumab crossovers. These effects were maintained from week 52 in VOYAGE 1 and week 100 in VOYAGE 2. No new safety signals were identified. Conclusions: Guselkumab maintains high levels of clinical response and improvement in patient‐reported outcomes through 5 years in patients with moderate‐to‐severe psoriasis.